Three-dimensional numerical simulation of the thermal and aerodynamic behavior of a roof structure built on a slope and used for horticultural production - Villagran, Edwin Andres; Bojaca, Carlos (Comunicata Scientiae, 2021)
In tropical countries, part of the horticultural production is carried out in hillside soils. In recent years, due to the adverse effects of climate change and other biotic factors that limit and affect agricultural production, the use of roof structures has been promoted as a technological means to improve production in this type of production system. The microclimate study of structures built on slopes is scarce, therefore farmers continue to build the same type of structure without technical design criteria and without knowing if the microclimate conditions generated are suitable for the crops. In the present research work, an experimentally validated 3D CFD numerical model was implemented to analyze air flows and spatial temperature behavior in a roof structure built on a site with broken topography. The results obtained allowed us to find that the air flows are strongly affected by the longitudinal and transversal slopes of the land, which produces low ventilation rates that generate thermal gradients above 8 °C and highly heterogeneous thermal behavior, factors that are not suitable for horticultural production.